2004
DOI: 10.1186/1741-7015-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evidence for an invasion-independent metastasis pathway exists in multiple human cancers

Abstract: Background: We have previously described an alternative invasion-independent pathway of cancer metastasis in a murine mammary tumor model. This pathway is initiated by intravasation of tumor nests enveloped by endothelial cells of sinusoidal vasculature within the tumor. In this study, we examined whether evidence for the invasion-independent pathway of metastasis is present in human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 17 publications
7
44
1
Order By: Relevance
“…Recently, morphological studies from our group and other groups have revealed the development of sinusoid-like vessels that closely surround individual tumor clusters in HCC. [22][23][24] We also find that the existence of a vessel-surrounded tumor cluster is significantly associated with the incidence of intravascular endothelium-coated emboli and predicts an early relapse of HCC. 22 These findings suggest that certain types of vascular pattern may have a profound impact on HCC metastasis.…”
mentioning
confidence: 60%
“…Recently, morphological studies from our group and other groups have revealed the development of sinusoid-like vessels that closely surround individual tumor clusters in HCC. [22][23][24] We also find that the existence of a vessel-surrounded tumor cluster is significantly associated with the incidence of intravascular endothelium-coated emboli and predicts an early relapse of HCC. 22 These findings suggest that certain types of vascular pattern may have a profound impact on HCC metastasis.…”
mentioning
confidence: 60%
“…Tumor tissue fragments may have high clinical relevance as these are frequently found in lymph and blood vessels of cancer patients with poor prognosis Weidner, 2002). Interestingly, renal clear cell carcinomas, which frequently show constitutive VEGF-A expression, also frequently display a nodular phenotype and intravascular growth (Sugino et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…First, clinical and animal data show that for metastatic tumors in brains, lungs or livers, induction of angiogenesis is not a prerequisite as for these tumors the preexistent vascular bed may allow tumor growth (Pezzella et al, 1997;Al-Mehdi et al, 2000;Neves et al, 2001;Vermeulen et al, 2001;Kim et al, 2002;Kusters et al, 2002;Passalidou et al, 2002;Auguste et al, 2005). Secondly, recent reports demonstrated the presence of intravascular endothelium-covered tumor cell clusters in the primary tumor as origin of metastasis (Sugino et al, 1993(Sugino et al, , 2002(Sugino et al, , 2004. Clinical and preclinical data suggest that not the amount of circulating single tumor cells but rather that of circulating tumor cell clusters correlate with development of metastases (Fidler, 1973;Liotta et al, 1976;Glaves, 1983;Vlems et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The VEGFR-3-expressing endothelial cells that envelope the LAM cell clusters may serve to shield mutation-bearing LAM cells from immune surveillance against novel or ectopic surface antigens they express, such as the glycolipid GD-3 (126). Long dwell times of these "tumor emboli" in the pulmonary capillaries may facilitate metastasis by a process similar to that proposed for the angiogenesis-driven, "invasion-independent" mechanism described for endothelial cell-lined renal cell carcinoma clusters that gain access to the interstitium via surrounding venules (127,128).…”
Section: Figurementioning
confidence: 99%